Spinal flexibility in idiopathic scoliosis: A quantitative approach to Grade I (facet joint osteotomy, FJO) and Grade II (ponte osteotomy, PO) osteotomy techniques - Yibing Liu; Zhenzhuo Zhang; Guomao Zhu; Jinqian Liang (Journal of Orthopaedic Surgery, 2025)
Purpose: The purpose of this study was to evaluate the role of preoperative spinal flexibility in guiding osteotomy selection for idiopathic scoliosis (IS) surgery. Specifically, it aimed to identify a flexibility threshold to optimize the decision-making process between Grade I (Facet Joint Osteotomy, FJO) and Grade II (Ponte Osteotomy, PO) osteotomy techniques. Methods: This retrospective study included 77 IS patients who underwent osteotomy surgeries performed by two experienced spine surgeons at our hospital between 2018 and 2023. Based on the osteotomy type, patients were divided into the FJO group ( n = 41) and the PO group ( n = 36). Demographic data, preoperative spinal flexibility (measured as the ratio of curve correction on bending X-rays to the standing Cobb angle), and surgical correction rates were compared. Restricted cubic spline (RCS) analysis was used to identify the flexibility threshold. Complication rates, hospital stay duration, and blood loss were also analyzed. Results: RCS analysis identified a flexibility threshold of 0.657. Below this threshold, PO achieved superior correction rates, while above it, FJO showed comparable correction outcomes with fewer complications, shorter hospital stays, and lower blood loss. Spinal flexibility was significantly correlated with surgical outcomes, and the type of osteotomy influenced correction rates and complication severity. Conclusion: Preoperative spinal flexibility is a critical factor in osteotomy selection for IS surgery. PO is recommended for flexibility <0.657, while FJO is preferred for higher flexibility. Flexibility-based surgical planning can improve correction outcomes, minimize complications, and enhance recovery in IS patients.